Photovoltaic effect in optical transitions for ultraquantum limit between spin areas of Landau levels - Chernyshov, N.N.; Slipchenko, N.I.; Belousov, A.V.; Alkhawaldeh, M.A.F. (Radiotekhnika, 2018)
The article is devoted to the investigation of the photovoltaic effect in GaAs under optical transitions between the spin sub-bands of the Landau levels for the ultra quantum limit. The geometry is considered, when the polarization is perpendicular, and the current is directed along the magnetic field. The effect is due to the cubic terms in the Hamiltonian that exist due to the absence of an inversion center. The dependence of the current on the magnetic field has a resonance nature. Such an effect is associated with resonance in the intermediate state and interference of the second-order transition amplitudes with respect to relativistic contributions to the Hamiltonian. The aim of the work is a theoretical and experimental study of the photovoltaic effect for spin resonance. The practical value and scientific novelty lies in the study of the photovoltaic effect at spin resonance. Since a weakly absorbing medium is considered, an increase in the photovoltaic effect is observed as a result of the divergence of the mean square electric field modulus. The practical significance of the results lies in the development of a methodology for studying band parameters, and the terms in the Hamiltonian can lead to electro dipole transitions and photocurrents.